2019
DOI: 10.1039/c8ta08083f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen loss and surface degradation during electrochemical cycling of lithium-ion battery cathode material LiMn2O4

Abstract: Atomic-resolution STEM and EELS analysis provide insights into microscopic mechanisms behind oxygen loss and capacity fade in spinel-structured lithium-ion battery cathode material LiMn2O4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 67 publications
6
73
1
Order By: Relevance
“…Such a surface structure, as presented in the atomic models (Fig. 6e ), could be considered as a cation-mixed Mn 3 O 4 -type structure 59 62 , which is likely due to S-deposition-induced Li leaching and subsequent TM ion migration, as predicted by our DFT calculations. The lowered delithiation voltage (by 1.6 V as compared with the bulk 15 ) in the S-deposited surface suggests that Li ions are easily leached out from the surface during the heat treatment.…”
Section: Resultsmentioning
confidence: 58%
“…Such a surface structure, as presented in the atomic models (Fig. 6e ), could be considered as a cation-mixed Mn 3 O 4 -type structure 59 62 , which is likely due to S-deposition-induced Li leaching and subsequent TM ion migration, as predicted by our DFT calculations. The lowered delithiation voltage (by 1.6 V as compared with the bulk 15 ) in the S-deposited surface suggests that Li ions are easily leached out from the surface during the heat treatment.…”
Section: Resultsmentioning
confidence: 58%
“…In the O K ‐edge spectra, prepeak (peak a) is ascribed to the hybridization between Mn 3d and O 2p levels. The intensity of this peak can reflect the O content in Mn coordination shell; [ 37,62,63 ] the weaker intensity means the more lacking of O (more oxygen vacancies). [ 37,62 ] In the Mn L 2,3 ‐edge spectra, peaks L 2 and L 3 can be attributed to the transitions from 2p 1/2 and 2p 3/2 core states to 3d unoccupied states localized on the exited Mn n + .…”
Section: Resultsmentioning
confidence: 99%
“…[ 40 ] The observed Mn dissolution under highly charged states indicates the surface instability of highly delithiated LiMn 2 O 4 and LiNi 0.5 Mn 1.5 O 4 , which could result in anion‐redox‐induced global oxygen mobility, [ 32 ] oxygen loss, TM reduction, and side reactions with the organic electrolytes. For example, with combined XPS, electron energy loss spectroscopy (EELS), scanning transmission electron microscopy (STEM), and density functional theory (DFT) calculations, Tang et al [ 48 ] reported the reduction of surface Mn upon charging and oxidation of surface Mn upon discharging, which is contrary to what are expected in the bulk; Gao et al [ 49 ] used atomic‐level STEM to directly characterize and visualize oxygen loss, Mn reduction, and surface reconstruction upon charging; using epitaxial LiMn 2 O 4 thin films, Hirayama et al [ 50 ] showed that surface instability/reconstruction and Mn dissolution are surface dependent and more pronounced at (110) than at (111) surface. These observations have shed light on the fundamental mechanism of high‐voltage instability of spinel cathodes, especially at the surface.…”
Section: Degradation Mechanisms Of Spinel Cathodesmentioning
confidence: 99%